Hydrogen generation by water electrolysis using carbon nanotube anode - Dubey P.K.; Sinha A.S.K.; Talapatra S.; Koratkar N.; Ajayan P.M.; Srivastava O.N. (My University, 2025)
Anode made of multiwalled carbon nanotubes (MWNT) results in enhancement of exchange current density compared to graphite anode in a conventional alkaline water electrolysis cell. The hydrogen production rate with the nanotubes was measured to be ∼375 lh-1 m-2 at pH ∼ 14 which was nearly double of that obtained from traditional graphitic carbon electrodes at the same overpotential. This effect appears to be caused by defects on the nanotubes which reduces the energy barrier for the dissociation of OH- into oxygen at the anode. © 2010 Professor T. Nejat Veziroglu.